Safety and Immunogenicity of Inactivated and Recombinant Protein SARS-CoV-2 Vaccines in Patients With Thyroid Cancer - Han, Yuling; Yang, Jiaxin; He, Danshuang; Feng, Yang; Liu, Xiaoman; Min, Yu; Fan, Shenghao; Yin, Guobing; Hu, Daixing (Frontiers in Immunology, 2022)
Background: This study was to assess the safety and immunogenicity of SARS-CoV-2 vaccines in patients with thyroid cancer. Methods: This observational study included thyroid cancer patients between April 1, 2021, and November 31, 2021, in the Second Affiliated Hospital of Chongqing Medical University. All participants received at least one dose of the SARS-CoV-2 vaccine. SARS-CoV-2 IgG was tested, and the interval time between the last dose and humoral response test ranged from <1 month to 8 months. The complications after SARS-CoV-2 vaccines were recorded. Results: A total of 115 participants at least received one dose of SARS-CoV-2 vaccines with a 67.0% IgG positive rate. Among them, 98 cases had completed vaccination, and the positivity of SARS-CoV-2 IgG antibodies was 96% (24/25) with three doses of ZF2001. SARS-CoV-2 IgG antibodies' positivity was 63.0% (46/73) of two doses of CoronaVac or BBIBP-CorV vaccine. Additionally, after four months of the last dose vaccination, the IgG positive rate (31.6%, 6/19) significantly decreased in thyroid cancer patients. The IgG positive rate (81.0%, 64/79) was satisfactory within three months of the last dose vaccination. Ten (10.2%) patients had side effects after SARS-CoV-2 vaccination. Among them, two (2.0%) patients had a fever, five (5.1%) patients had injection site pain, one (1.0%) patient felt dizzy, and one patient felt dizzy and had injection site pain at the same time. Conclusion: SARS-CoV-2 vaccines (CoronaVac, BBIBP-CorV, and ZF2001) are safe in thyroid cancer patients. The regression time of SARS-CoV-2 IgG is significantly shorter in thyroid cancer patients than in healthy adults. Therefore, a booster vaccination dose may be earlier than the systematic strategy for thyroid cancer patients.